2022
DOI: 10.3389/fpubh.2022.658826
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Worker Perspectives of HIV Pre-exposure Prophylaxis Service Delivery in Central Uganda

Abstract: BackgroundScale-up of HIV pre-exposure prophylaxis (PrEP) services in Uganda is ongoing. However, health care workers (HCWs) may not be aware of PrEP nor what offering this service entails. We explored the impact of standardized HCW training on the knowledge and perspectives of PrEP service delivery in Uganda.MethodsWe recruited HCWs from facilities that offered HIV-related services in Central Uganda. Using the Uganda Ministry of Health curriculum, we trained HCWs on PrEP services. We collected data about PrEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
1
Order By: Relevance
“…Las acciones preventivas identificadas forman parte de la prevención combinada, es decir, estrategias que pueden ser adoptadas simultáneamente (4) . Son conductas basadas en la pareja aunque haya estrategias preventivas individuales, como el asesoramiento (individual y con los parejos) que puede ser asociado a otras conductas como las consultas de enfermería, antes y después de las pruebas rápidas; suministro de PrEP y PEP para la pareja VIH negativo; tratamiento con antirretrovirales de PVHIV; además de las actividades de educación en salud para concientización de las parejas y de su red familiar (4,20) .…”
Section: Discussionunclassified
“…Las acciones preventivas identificadas forman parte de la prevención combinada, es decir, estrategias que pueden ser adoptadas simultáneamente (4) . Son conductas basadas en la pareja aunque haya estrategias preventivas individuales, como el asesoramiento (individual y con los parejos) que puede ser asociado a otras conductas como las consultas de enfermería, antes y después de las pruebas rápidas; suministro de PrEP y PEP para la pareja VIH negativo; tratamiento con antirretrovirales de PVHIV; además de las actividades de educación en salud para concientización de las parejas y de su red familiar (4,20) .…”
Section: Discussionunclassified
“…The studies included in this review also demonstrated the structural barriers at the provider level. HCWs, as the key population in the delivery of PrEP, their knowledge, attitudes, and concerns were determinants of the successful implementation of PrEP ( 49 , 50 ). However, the findings showed that HCWs’ knowledge of PrEP should be strengthened, as they were unclear on how to accurately prescribe PrEP, and even failed to differentiate PrEP and PEP ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each participant took part in a single in-person qualitative interview guided by a semi-structured discussion guide (Additional file 1). The guide was developed collaboratively by the research team based on literature reviews, previous experiences working with PWUD and PWID populations in other settings, and knowledge of existing PrEP and harm reduction service delivery models and programs [19][20][21][22][23][24]. Participant interviews covered: (1) drug use experiences, (2) harm reduction knowledge and experiences, (3) HIV risk and risk perception, (4) knowledge and use of oral PrEP, and (5) perspectives of COVID-19 mitigation measures.…”
Section: Data Collectionmentioning
confidence: 99%